Czeskie czasopisma i ich czytelnicy (w świetle badań czytelnictwa) = Czech magazines and their readers (in the light of readership research) - Trávníček, Jiří (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article attempts to answer the question of who reads magazines. The starting point is three statistical surveys carried out in 2007, 2010 and 2013, as well as parallel quality tests (readers? life profiles) from 2009 to 2015. As for the range of magazines, it covers the period from the 1980s to 2016. Sociodemographic data is presented on the basis of which the main characteristics of a magazine reader can be outlined. The reader of magazines is compared with a book reader, revealing barriers that the first and the second one encounter. It turns out that reading magazines does not pose such huge socio-geographic barriers as book reading; it is a more widespread category, with a wider range.
Keywords: czytelnik; czasopisma czeskie; czytelnictwo; czytelnictwo prasy; czytelnictwo książek; Reader; Czech magazines; reading; press reading; book reading